2015
DOI: 10.1371/journal.pone.0118450
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Embryo Patterning and Precision in Drosophila Segmentation: Krüppel Dual Regulation of hunchback

Abstract: In early development, genes are expressed in spatial patterns which later define cellular identities and tissue locations. The mechanisms of such pattern formation have been studied extensively in early Drosophila (fruit fly) embryos. The gap gene hunchback (hb) is one of the earliest genes to be expressed in anterior-posterior (AP) body segmentation. As a transcriptional regulator for a number of downstream genes, the spatial precision of hb expression can have significant effects in the development of the bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 82 publications
(139 reference statements)
2
22
0
Order By: Relevance
“…5(b)]. This corroborates our¯nding of dual regulation in an earlier project, 55 which used a non-GA approach to¯t a BS-level \¯ne-grained" model of hb regulation. Dual regulation is supported by a number of in vitro studies on Hb-Kr interactions, and also accounts for loss of Hb PS4 in Kr À mutants.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…5(b)]. This corroborates our¯nding of dual regulation in an earlier project, 55 which used a non-GA approach to¯t a BS-level \¯ne-grained" model of hb regulation. Dual regulation is supported by a number of in vitro studies on Hb-Kr interactions, and also accounts for loss of Hb PS4 in Kr À mutants.…”
Section: Resultssupporting
confidence: 81%
“…Dual regulation has been shown to have the capacity to reduce expression hb noise in the PS4 region. 55 Equation 4 WT solutions also included a Kni repression term to limit hb production on the posterior side of the Kr peak; modeling kni À mutants required repression by an additional term in the Kni peak region (in the \extended" È 1 Þ, such as the Nub TF (see Fig. 3(b); TFs at this position include Nub (also called pdm-1), pdm-2, and BLIMP-1 [55][56][57] ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…See also Sanchez et al and Monteoliva et al [40,45] on the effect of the number of BSs on transcriptional noise. For later patterning, we modeled the gap-gap interactions producing the mid-embryo Hb concentration peak necessary for the future thorax [46]. Stochastic simulations indicated that hb-Kr interactions reduce expression noise and contribute to the reliability of mid-embryo development, predicting that FISH dot-dot correlation should decrease in Kr − mutants.…”
Section: Modelingmentioning
confidence: 99%